Analisis Tingkat Kepuasan Pengguna Sistem Informasi Perpustakaan Dengan Pendekatan Pieces Framework - Ari Fattah Fuaddin; Fisabilla Tidar Yoga Pratama; Fakhrul Akif Maulana Putra; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to analyze the level of user satisfaction with the Library Information System using the PIECES Framework approach. This method includes six main indicators: Performance, Information, Economics, Control and Security, Efficiency, and Service. Data were collected through questionnaires distributed to 30 respondents consisting of library managers and users. The results showed that all indicators were SATISFIED with an average satisfaction score of 3.46. The Control and Security indicator obtained the highest score with a value of 3.93, while Service was the indicator with the lowest value, namely 3.51. In general, the Library Information System is considered to have fast, accurate, and efficient performance in supporting library management. However, there are several inputs related to service features that need to be improved, especially to facilitate new users. The results of this study confirm that the PIECES Framework is effective for evaluating user satisfaction, providing comprehensive guidance for information system analysis. The findings of the study are expected to be a reference for the development of library information systems in the future to improve service quality and operational efficiency.